Customer and employee perceptual congruence in service co-production. Issue 1 (2nd January 2019) - Ozkul, Ahmet Semih; Damali, Uzay; Nandialath, Anup Menon; Stapleton, Andrew
Abstract: Building on perceptual congruence research, this paper argues that when a customer and a front-line employee have similar perceptions of a co-produced output, employee awareness can support quality improvement efforts in service operations. The authors develop an analytical model describing perceptual congruence in a dyadic customer-employee relationship using a constant elasticity of substitution (CES) function. This model allows the authors to describe a service context with three factors: 1) customer work-allocation level (that is, percent of work expected to be done by the customer); 2) customer-employee interaction level (that is, level of communication needed); and 3) customer-employee interaction type (that is, superiority or inferiority perceived by the customer and the employee in the interaction). The authors also calculate which type of customer-employee perceptual bias alignment is needed to achieve perceptual congruence under these three contextual factors. Their model may guide service managers how to manage perceptual biases -- considering their service design characteristics to achieve perceptual congruence.